Rethinking Family Practices - Morgan, D. author. aut Link
VIII, 189 p.
Keywords: Leading family sociologist David Morgan revisits his highly influential 'family practices' approach in this new book. Exploring its impact, and how it has been critiqued, Morgan shows the continued relevance of the approach with reference to time and space, the body, emotions, ethics and work/life balance.